Vitamin supplementation and its effect on incident type 1 diabetes mellitus and islet autoimmunity: a systematic review and meta-analysis - Low, Chen Ee; Chew, Nicole Shi Min; Rana, Sounak; Loke, Sean; Chin, Run Ting; Kao, Shih Ling; Lee, Ainsley Ryan Yan Bin; Tay, Sen Hee (Frontiers in Immunology, 2025)
IntroductionThe prevalence of type 1 diabetes mellitus (T1DM) is set to rise annually with long-term implications on the quality-of-life. Supplementation with vitamins has garnered interest in recent years due to its association with the development of islet autoimmunity (IA) and T1DM. This systematic review aims to investigate the relationship between vitamins supplementation on the development of IA or T1DM or progression of IA to T1DM.MethodsThis PRISMA-adherent systematic review involved a systematic search of PubMed, Embase and Cochrane for all studies that evaluated the odds (pre-calculated pooled OR) and risk (RR) of IA, T1DM, or progression of IA to T1DM after supplementation with vitamins. Random effects meta-analyses were used for primary analysis.Results15 studies were included. Meta-analyses observed that vitamin D did not modify the odds of developing T1DM (Pooled OR=0.55, 95%CI: 0.22-1.38) or IA (Pooled OR=0.91, 95%CI: 0.67-1.25). The relative risk of developing T1DM was almost significant (RR=0.66, 95%CI: 0.41-1.06), emphasizing the need to conduct further large-scale cohort studies. Systematic review revealed that vitamin B supplementation did not influence the risk of T1DM and progression of IA to T1DM. Additionally, there was an association between higher maternal education levels and higher levels of vitamin D supplementation in their offspring.ConclusionIn conclusion, we found no significant benefit with the use of various vitamins in modifying the risk of developing IA, T1DM or progression of IA to T1DM. Our study provides a foundation for future research by contributing to the evolving landscape of nutritional immunology.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024540524.